Consumer trends (Henry Stewart Talks, 2026)
Consumer trends and behaviors, Digital tech and mobile impact, Producer and consumer boundaries, Online reviews and social sharing, Experience-led brand interactions, Transparency, authenticity, and trust, Agility and omnichannel approaches, Corporate responsibility and sustainability